Effect of Vacuum Packaging on Hardness of Kradi cheese stored at different - Punoo, Hilal Ahmad (Indian Journal of Dairy Science, 2023)
This study investigated changes in hardness property of kradi cheese stored under vacuum and normal conditions at 25oC, 5oC and Â -20oCÂ at different intervals. At 25oC storage temperature hardness was affected by atmosphere whereas storage periods did not affected hardness of samples. At 5oC storage temperature both atmospheres as well as storage periods affected the hardness of samples. At -20oC storage temperature, it was observed that both atmosphere as well as storage periods affected the hardness of stored samples. Hardness in normal packed samples decreased more as compared to vacuum packed samples. The vacuum packaging retarded textural changes related to hardness in comparison to normal packaging.